The Effect Of Attractiveness Factors On Mall Shoppers’ Satisfaction In Jordan - Habbosh, Thair Abed Alrahman Mohamed (2013)
Shopping malls have turned into be a vibrant milieu for business with a wide–ranging impact on traders, retailers, and shoppers, who are attracted to modern malls not only to do shopping, but also to enjoy the recreational facilities and services. Due to the growing interest of shoppers in shopping malls in Jordan, and to the importance of such project to the overall economy of the country as a whole, it has become contingent to examine the current statues of both shopping malls and shoppers' interests and desires to achieve an utter success in various related walks. In this vein, it has been noticed that only few studies have investigated the effect of attractiveness factors on shoppers' satisfaction in Jordan. Accordingly, the researcher has stepped forward to bridge the gap of lack of updated knowledge in this respect. That is to say, the present study will tackle in detail the effect of eight attractiveness factors on shoppers' satisfaction in selected Jordanian malls. Such a study requires first identifying the available attractive factors in the selected malls. Second, showing the extent to which the available attractiveness factors affect achieving shoppers' satisfaction. For the purpose of achieving the objectives of this study, questionnaire surveys have been used to measure shopper's satisfaction. The questionnaire instruments are an adaptation of the previous studies'. They contain (57) items distributed on (9) domains. As for the sample of the study, it consists of (775) shoppers who visit malls frequently. The chosen malls represent the biggest four malls in Jordan. These include the following: Mecca Mall, Mukhtar Mall, Sameh Mall and Arabella Mall.